Hypervitaminosis A in type 2 diabetes and its relation with renal function and cardiovascular complications - Anna Toffalini; Nicolò Vigolo; Elena Sani; Elisa Paviati; Matteo Gelati; Elisa Danese; Giacomo Zoppini (PLoS ONE, 2025)
Vitamin A is a fundamental micronutrient in the diet. In recent years, hypervitaminosis A has been described in subjects, mainly children, with renal dysfunction. The aim of the present study was to estimate the prevalence of hypervitaminosis A in adult patients affected by type 2 diabetes and to evaluate the associated factors. This cross-sectional observational study included 200 ambulatory patients affected by type 2 diabetes regularly attending the Diabetes Clinic of Verona (Italy). Eligible patients were consecutively enrolled. Vitamin A was measured by reverse phase high performance liquid chromatography with UV detection. The normal range of values for vitamin A concentrations was 1.04–2.79 μmol/L. All other laboratory parameters were measured by standard methods. A multivariate logistic regression model was applied to study the factors independently associated with the hypervitaminosis A. Hypervitaminosis A was detected in 29% of our cohort of patients. Its prevalence was significantly higher in patients with cardiovascular complications (CVD). Nevertheless, when patients with CVD were stratified according to renal function, the latter emerged as the main factor associated with hypervitaminosis A. The multivariate analysis confirmed that estimated glomerular filtration rate was an independent predictor of hypervitaminosis A (0.97 CI 95% 0.96–0.99, p = 0.008).The main alteration of vitamin A in ambulatory patients affected by type 2 diabetes is hypervitaminosis. Renal function is strongly associated with hypervitaminosis A.